A review of the performance of infilled RC structures in recent earthquakes - Furtado, André (2021)
The primary objective is to present the most representative types of damage observed in reinforced concrete (RC) structures due to earthquakes. Those damages are divided according to the ten most representative types. Examples and the main reasons that could trigger each failure mechanism are presented. The definition of these damage types is supported by post-earthquake damage reconnaissance missions in Sichuan (China) in 2008, L’Aquila (Italy) in 2009, Lorca (Spain) in 2011, Emilia-Romagna (Italy) in 2012, Gorkha (Nepal) in 2015, Muisne (Ecuador) in 2016 and Chiapas (Mexico) in 2017. An extensive discussion is presented concerning the infill walls’ seismic behaviour and their interaction with the RC structural elements. The presentation of the significant learnings and findings concerning the typical damage herein presented and discussed are compared with the common Southern European construction practice. The impact of the infill walls on the rehabilitation costs of damaged RC buildings is also studied. These costs are compared to those related to the structural damage and rehabilitation of the entire building structure to understand the impact of the infill walls. Finally, a case study is presented to study the effect of implementing simplified retrofitting strategies to prevent the soft-storey mechanism, one of the most common problems observed in past earthquake events.